An evaluation of online food delivery application: fuzzy analytical hierarchy process / Nur Solihah Khadhiah Abdullah ... [et al.] - Abdullah, Nur Solihah Khadhiah; Mohd Asri, Nurul Izzati; Jaafar, Ruhana; Hassanuddin, Nor Aini (Universiti Teknologi MARA, Perak, 2024)
Food delivery is one of the businesses reporting growth rates after the COVID-19 pandemic. Due to social isolation and extensive lockdowns worldwide, individuals who once dined out now choose online food delivery. To keep up with the ever-changing market dynamics, the service provider must be aware of various measurements and aspects related to sustainable growth. Therefore, this study aims to determine the criteria for evaluating online food delivery applications, calculate the weight for criteria, and rank the online food delivery applications according to the most preferred by the customers. This study uses a multi-criteria decision-making (MCDM)-based framework which is the Fuzzy Analytic Hierarchy Process (FAHP). The FAHP is used to produce weights for criteria by applying fuzzy set theory to the linguistic evaluation statements of experts and ranking the online food delivery applications according to the customer's preference. The findings indicate that Foodpanda is the most preferred food delivery application, followed by GrabFood and McDelivery. The most crucial main criterion is economics, with delivery cost as the priority sub-criteria. The second most important criterion is technology, the third is service quality, and the last is social and environmental. This study is useful for the service provider in improving the criteria that will most affect the customer, as well as for the customer to wisely choose the e-service application that meets their demand.